One-Pot Synthesis of 2-Sulfonamidobenzo[b]thiophenes Enabled by a Mild Protonative Activation of Ynamides - Kim, Solbin; Lim, So Yeun; Kwak, Kihun; Lim, Hee Nam; Yeom, Hyun-Suk (Synthesis, 2022)
The silica gel promoted or solvent-promoted protonative intramolecular cyclization of ynamides containing an o-(methylthio)aryl group resulted in the one-pot formation of biologically important benzo[b]thiophenes. Compared with ynamide activation methods that use strong Brønsted acids or expensive transition metals, this protocol is mild and economical. Due to these merits, various functionalized 2-amidobenzo[b]thiophenes were furnished in a convenient way.
Keywords: ynamides; one pot; electrophilic cyclization; benzo[b]thiophenes; silica gel assisted